Integrating Economy, Energy, Air Pollution in Building Renovation Plans. Issue 5 (2018) - Guariso, Giorgio; Sangiorgio, Matteo
Abstract: Residential buildings represent a considerable portion of the energy demand of a temperate country. Old European regions, where most of the buildings were often built in periods of low energy prices, have a large margin for improvement. The study shows how energy saving measures can be optimally planned at regional level, taking into account the specific features of the building stock, and what the consequences of an optimal choice are in economic and environmental terms.